STRATEGY IMPLEMANTATION AND ORGANIZATIONAL PERFORMANCE: A CASE STUDY OF KENYA MEDICAL TRAINING COLLEGE - Muendo, Mutua Caleb; Ogutu, Prof. Martin (European Journal of Business and Strategic Management, 2020)
Purpose: The objective of this study was to determine the strategies applied by KMTC and the performance of the organization. Materials and Methods: The study adopted a case study research design. The research utilized both secondary and primary data. Primary data was collected from senior managers namely: Former Strategic Plan In-charge, Deputy Director Finance and Administration, Human Resource Manager, External Liaison Officer, Public Relation Officer, Deputy Registrar Research, Chief Procurement Officer and the Institutional Advancement Officer. Secondary data was collected through desk review of the strategic plans implementation and financial reports. The nature of data collected was qualitative and was therefore analyzed using content analysis technique. Results: The empirical findings and analysis conducted in KMTC shows that strategic Implementation directly contributes to organizational performance. The study concludes that strategy implementation and organization performance in KMTC involves drawing from national context and global plans and priorities to shape and ensure strategy alignment and relevance. Unique contribution to theory, practice and policy: The study recommended that KMTC should institute an operational office specifically dedicated to strategic planning processes. The organization should improve awareness of the strategic plan at different levels through launching and proper dissemination; it should also support participatory planning and implementation of project activities within the organization with the aim of enhancing the performance. Additionally, the organization needs to allocate adequate resources needed to realize the different key result areas in the strategic plan and thus actualize the targeted objectives.